( 3 / 4 )( 8 x + 4 x ) + 5 y + 4 = ( 2 / 3 )( 12 x + 9 ) =
3 * 8 x / 4 + 3 * 4 x / 4 + 5 y + 4 = 2 * 12 x / 3 + 9 * 2 / 3 =
3 * 2 * 4 x / 4 + 3 * 4 x / 4 + 5 y + 4 = 2 * 4 * 3 x / 3 + 3 * 3 * 2 / 3 =
3 * 2 * x + 3 * x + 5 y + 4 = 2 * 4 * x + 3 * 2 =
6 x + 3 x + 5 y + 4 = 8 x + 6
9 x + 5 y + 4 = 8 x + 6 Subtract 9 x to both sides
9 x + 5 y + 4 - 9 x = 8 x + 6 - 9 x
5 y + 4 = - x + 6 Subtract 4 to both sides
5 y + 4 - 4 = - x + 6 - 4
5 y = - x + 2 Divide both sides by 5
y = ( - x + 2 ) / 5
Solve for y (3/4)(8x+4x)+5y+4=(2/3)(12X+9)
1 answer